2015
DOI: 10.1002/pssb.201552572
|View full text |Cite
|
Sign up to set email alerts
|

Switching between two types of auxetic behavior of two-dimensional periodic cells with square rotation

Abstract: Auxetic materials and related systems with negative Poisson's ratios have recently received physical and mathematical interest. Their mechanical properties induced by particular solid deformations are expected to allow remarkable advances to be made in the field of engineering. In our previous study, we proposed a structural unit that transforms into two types of diamond‐ and square‐patterned cells and discussed its bi‐stiffness property [Proc. R. Soc. A 469, 20130063 (2013)]. In this study, we applied the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…For example, an array of rotating rigid units can induce auxetic behavior, and this is one of the fundamental auxetic mechanisms according to some background on geometry3031323334353637. Many auxetic cellular and laminated composite solids can be designed from considerations of geometry and rotation3738394041424344.…”
mentioning
confidence: 99%
“…For example, an array of rotating rigid units can induce auxetic behavior, and this is one of the fundamental auxetic mechanisms according to some background on geometry3031323334353637. Many auxetic cellular and laminated composite solids can be designed from considerations of geometry and rotation3738394041424344.…”
mentioning
confidence: 99%
“…We further extend this structure to create a periodic structure by joining and inserting linear springs between adjacent unit cells. Finite-element analyses demonstrated that the periodic structure also has a similar transition mechanism [ 56 ]. In this instance, the deflection of each cell plays a major role in the transition from one motion to another.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations suggest that the auxetic behavior involves rotational deformation of the unit cells in auxetic structures. [22,[57][58][59][60] Thus, the essence of our work is to design the internal structure with such rotational deformation characteristics. Some holes were set in the model to allow the rotation of internal units of the material during deformation.…”
Section: Psf Methodsmentioning
confidence: 99%